THE GULF WAR REVISITED:: ISSUES AND CONTRIBUTIONS TO THE ART OF WAR - Opeyeoluwa, Rotimi Olajide (Journal of Contemporary International Relations and Diplomacy, 2021)
This paper examines the 1991 Gulf War and how it contributed to the development of the art of war since the dawn of the post-Cold War realities. The 1991 Gulf War was a war waged by a coalition force of 40 nations led by the United States of America (USA) against Iraq in response to Iraq’s invasion and subsequent annexation of Kuwait, arising from oil pricing and production disputes. This article seeks an explanation for how the Gulf War has contributed to the art of war by explaining how the Napoleonic strategy of quick and decisive victory was used in the operation. This strategy contrast sharply with the intention of Iraq for a sustained all-drawn-out war, which is meant to wear out their opponents. The article analyses the further consequences of this conceptual clash in military doctrine. It explains that the contrast between both concepts and especially the western military culture for fighting wars was the decisive element in the Gulf War. In carrying out this research, secondary sources were consulted and used accordingly. The research findings show the contribution of the 1991 Gulf War to the increasing complexities of war. The war further demonstrated the validity of the collective security system as the coalition forces were able to restore Kuwait’s sovereignty. In addition, the study is relevant as it exposed the challenges posed by warfare and the vulnerabilities it poses in inter-state relations and on the international system.